An improved anatomical MRI technique with suppression of fixative fluid artifacts for the investigation of human postmortem brain phantoms. Issue 3 (7th March 2016) - Droby, Amgad; Yuen, Kenneth Sung Lai; Schänzer, Anne; Spiwoks‐Becker, Isabella; Acker, Till; Lienerth, Bianca; Zipp, Frauke; Deichmann, Ralf
Abstract : Purpose: Phantoms are often used to assess MR system stability in multicenter studies. Postmortem brain phantoms best replicate human brain anatomy, allowing for a combined assessment of the MR system and software chain for data analysis. However, a wash‐out of fixative fluid affecting T1 values and thus T1‐weighted sequences such as magnetization‐prepared 180 degrees radiofrequency pulses and rapid gradient‐echo (MP‐RAGE) has been reported for brain phantoms, hampering their immediate use. The purpose of this study was the creation of anatomical data that provide the characteristics of conventional data while avoiding this artifact. Theory and Methods: Two brain phantoms were scanned at several time points, acquiring conventional MP‐RAGE data and quantitative T1 and proton density (PD) maps. Assuming a suitable cutoff value T1cut, synthetic MP‐RAGE data were created from these maps, being T1‐weighted for T1 > T1cut to reduce fluid signal in the sulci, but PD‐weighted for T1 < T1cut for artifact suppression. Results: A time‐dependent artifact was observed in the T1 but not in the PD maps. The temporal stability of the synthetic data was greatly improved as compared to the conventional data. Conclusion: The proposed method enables anatomical imaging of postmortem brain phantoms, avoiding artifacts induced by the wash‐out of fixative fluid, and thus achieving high signal stability shortly after fixation. Magn Reson Med 77:1115–1123, 2017. © 2016 International Society for Magnetic Resonance in Medicine